Calibration of initial measurements from the full aperture backscatter system on the National Ignition Facility - Kirkwood, R; Mccarville, T; Froula, D; Young, B; Bower, D; Sewall, N; Niemann, C; Schneider, M; Moody, J; Gregori, G; Holdener, F; Chrisp, M; et al. (2004)
The full aperture backscatter system provides a measure of the spectral power, and integrated energy scattered by stimulated Brillouin (348-354 nm) and Raman (400-800 nm) scattering into the final focusing lens of the first four beams of the NIF laser. The system was designed to provide measurements at the highest expected fluences with: (1) spectral and temporal resolution, (2) beam aperture averaging, and (3) near-field imaging. This is accomplished with a strongly attenuating diffusive fiber coupler and streaked spectrometer and separate calibrated time integrated spectrometers, and imaging cameras. A new technique determines the wavelength dependent sensitivity of the complete system with a calibrated Xe lamp. Data from the calibration system are combined with scattering data from targets to produce the calibrated power and energy measurements that show significant corrections due to the broad band calibrations. (C) 2004 American Institute of Physics.